In vivo 5-HT6 and 5-HT2A receptor availability in antipsychotic treated schizophrenia patients vs. unmedicated healthy humans measured with [11C]GSK215083 PET. (30th January 2020) - Radhakrishnan, Rajiv; Matuskey, David; Nabulsi, Nabeel; Gaiser, Edward; Gallezot, Jean-Dominique; Henry, Shannan; Planeta, Beata; Lin, Shu-fei; Ropchan, Jim; Huang, Yiyun; Carson, Richard E; D'Souza, Deepak Cyril
Highlights: Lower 5-HT6 and 5-HT2A availability was seen in patients treated with olanzapine. Quetiapine resulted in a significantly lower 5-HT6 availability in the putamen. Risperidone resulted in significantly lower 5-HT2A availability in frontal cortex. Atypical antipsychotics resulted in distinct in-vivo 5-HT6 and 5-HT2A availability. Abstract: While 5-HT6 receptor is a potential therapeutic target for cognitive impairment in schizophrenia (SCZ), in vivo 5-HT6 receptor availability following antipsychotic treatment has not been examined to-date. We examined the availability of 5-HT6 and 5-HT2A receptors following treatment with olanzapine, risperidone, aripiprazole and quetiapine in male patients with SCZ vs unmedicated age-matched healthy male controls (HC) using positron emission tomography (PET) imaging with [ 11 C]GSK215083. [ 11 C]GSK215083 has been shown to have selectivity for 5-HT6 in the striatum and 5-HT2A in the cortex. Patients with SCZ ( n = 9) were scanned with [ 11 C]GSK215083 on HR+ PET scanner at presumed steady-state trough and peak serum levels following 7 days of confirmed inpatient antipsychotic treatment. Time-activity curves in regions-of-interest were fitted with multilinear analysis-1 (MA1). Regional nondisplaceable binding potential ( BP ND ) values were calculated using cerebellum as the reference region and corrected for partial volume effects. Compared to HCs ( n = 9), olanzapine was associated with significantly lower BP ND (range: 53%-95%) in ventral striatum, putamen, caudate and frontal cortex at both trough and peak scans. Risperidone was associated with significantly lower BP ND in frontal cortex at both trough and peak scans. The study provides preliminary evidence that treatment with different second-generation antipsychotics results in differing profiles of 5-HT2A and 5-HT6 availability.